Metal Organic Framework: Design of Hydrophilic Metal Organic Framework Water Adsorbents for Heat Reallocation (Adv. Mater. 32/2015). (20th August 2015) - Cadiau, Amandine; Lee, Ji Sun; Damasceno Borges, Daiane; Fabry, Paul; Devic, Thomas; Wharmby, Michael T.; Martineau, Charlotte; Foucher, Damien; Taulelle, Francis; Jun, Chul‐Ho; Hwang, Young Kyu; Stock, Norbert; et al.
<x xml:space="preserve">Abstract</x> On page 4775, J.‐S. Chang, C. Serre, and co‐workers design and synthesize a new scalable hydrophilic metal–organic framework material built up from a bio‐renewable linker named MIL‐160, showing outstanding water‐sorption properties, as highlighted by a comparison with the benchmark of each family of porous solids envisaged so far for applications in adsorption‐driven heat pumps and chillers.